Measuring the safety culture among the maintenance workers in railway station / Asmatu Salwa Suboh and Mohd Fadzli Mustaffa - Suboh, Asmatu Salwa; Mustaffa, Mohd Fadzli (2019)
Safety culture plays the crucial role in the workplace especially technical working. Some of the workers are not adhere to the rules and the guidelines which make the high chances towards the possibility accidents can occurred. This paper discussed on the problems of inability of maintenance workers to conduct their works in safe behaviour and ignored the importance of safety culture railway station. Rail transportation have been improved due to the technology advanced, thus safety culture need to be taken serious. The purpose of this study are 1) to identify the indicators of safety culture among the maintenance workers in railway station and 2) to measure the safety culture among maintenance workers in railway station. In order to achieve the objectives, the quantitative method has been done and the questionnaires were distributed to gather all the information to the maintenance workers in maintenance department of the railway station. The questionnaires covered all the indicators of safety culture that being identified based on the previous research. The result shows the individual behaviour indicator has the highest level of safety culture in the KTMB Kuala Lumpur Central.